Treatment of lingual traumatic ulcer accompanied with fungal infections - Sella Sella; Mochamad Fahlevi Rizal (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Traumatic ulcer is a common form of ulceration occured in oral cavity caused by mechanical trauma, either acute or chronic, resulting in loss of the entire epithelium. Traumatic ulcer often occurs in children that are usually found on buccal mucosa, labial mucosa of upper and lower lip, lateral tongue, and a variety of areas that may be bitten. To properly diagnose the ulcer, dentists should evaluate the history and clinical description in detail. If the lesion is allegedly accompanied by other infections, such as fungal, bacterial or viral infections, microbiological or serological tests will be required. One of the initial therapy given for fungal infection is nystatin which aimed to support the recovery and repair processes of epithelial tissue in traumatic ulcer case. Purpose: This case report is aimed to emphasize the importance of microbiological examination in suspected cases of ulcer accompanied with traumatic fungal infection. Case: A 12-year-old girl came to the clinic of Pediatric Dentistry, Faculty of Dentistry, University of Indonesia on June 9, 2011 accompanied with her mother. The patient who had a history of geographic tongue came with complaints of injury found in the middle of the tongue. The main diagnosis was ulcer accompanied with traumatic fungal infection based on the results of swab examination. Case management: This traumatic ulcer case was treated with Dental Health Education, oral prophylaxis, as well as prescribing and usage instructions of nystatin. The recovery and repair processes of mucosal epithelium of the tongue then occured after the use of nystatin. Conclusion: It can be concluded that microbiological examination is important to diagnose suspected cases of ulcer accompanied with traumatic fungal infection. The appropriate treatment such as nystatin can be given for traumatic fungal infection.Latar belakang: Ulkus traumatic merupakan bentuk umum dari ulserasi rongga mulut yang terjadi akibat trauma mekanis baik akut maupun kronis yang mengakibatkan hilangnya seluruh epitel. Ulkus traumatic sering terjadi pada anak-anak, biasanya ditemukan pada mukosa bukal, mukosa labial bibir atas dan bawah, lateral lidah, dan berbagai daerah yang mungkin dapat tergigit. Untuk mendiagnosis ulkus dengan tepat, dokter gigi harus mengevaluasi riwayat dan gambaran klinis secara detil dan jika lesi tersebut diduga disertai infeksi lainnya seperti fungal, bakteri atau virus maka diperlukan tes mikrobiologi atau serologi. Salah satu terapi awal jika diketahui adanya keterlibatan fungal dapat digunakan nystatin untuk mendukung pemulihan dan perbaikan jaringan epitel pada ulkus traumatic tersebut. Tujuan: Laporan kasus ini bertujuan untuk menekankan pentingnya pemeriksaan mikrobiologi pada kasus ulkus traumatic yang diduga disertai infeksi fungal. Kasus: Seorang anak perempuan usia 12 tahun datang ke klinik Ilmu Kedokteran Gigi Anak Fakultas Kedokteran Gigi Universitas Indonesia pada tanggal 9 Juni 2011 diantar ibunya. Pasien dengan riwayat geographic tongue datang dengan keluhan terdapat luka di bagian tengah lidah. Diagnosis utama adalah ulkus traumatic yang disertai infeksi fungal. Penegakan diagnosis ditetapkan dari hasil pemeriksaan swab. Tatalaksana kasus: Kasus ulcus traumatic ini diatasi dengan Dental Health Education, oral profilaksis, pemberian resep dan instruksi pemakaian nystatin. Terjadi pemulihan dan perbaikan epitel mukosa lidah setelah penggunaan nystatin. Kesimpulan: Pemeriksaan mikrobiologi penting dilakukan untuk menegakkan diagnosa ulkus traumatic yang diduga disertai infeksi fungal. Pengobatan yang tepat seperti pemberian nystatin dapat diberikan pada kasus ulkus traumatic yang disertai infeksi fungal.